2017
DOI: 10.1007/jhep09(2017)011
|View full text |Cite
|
Sign up to set email alerts
|

Gauge invariants, correlators and holography in bosonic and fermionic tensor models

Abstract: Motivated by the close connection of tensor models to the SYK model, we use representation theory to construct the complete set of gauge invariant observables for bosonic and fermionic tensor models. Correlation functions of the gauge invariant operators in the free theory are computed exactly. The gauge invariant operators close a ring. The structure constants of the ring are described explicitly. Finally, we construct a collective field theory description of the bosonic tensor model.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 108 publications
3
57
0
Order By: Relevance
“…Indeed, some studies addressing the connection between the RMT properties of SYK and the OTOCs appeared in recent days: very recently, [58] has studied the onset of RMT behavior in the (Gaussian filtered) SYK SFF 6 and found that, in agreement with the results of [59], the time-scale at which the RMT behavior appears -which we will call Thouless time -is not the 4 Indeed, a priori there could be systems which are chaotic according to one definition and not chaotic according to the other. 5 For example, see the U (1) symmetry and flavor generalizations [16][17][18][19][20][21], supersymmetric generalizations [22][23][24][25][26][27], SYK(-like) models without disorder [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43], gravity duals [44][45][46][47][48][49][50][51] and the Schwarzian theory [52][53][54]. 6 As we will revi...…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, some studies addressing the connection between the RMT properties of SYK and the OTOCs appeared in recent days: very recently, [58] has studied the onset of RMT behavior in the (Gaussian filtered) SYK SFF 6 and found that, in agreement with the results of [59], the time-scale at which the RMT behavior appears -which we will call Thouless time -is not the 4 Indeed, a priori there could be systems which are chaotic according to one definition and not chaotic according to the other. 5 For example, see the U (1) symmetry and flavor generalizations [16][17][18][19][20][21], supersymmetric generalizations [22][23][24][25][26][27], SYK(-like) models without disorder [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43], gravity duals [44][45][46][47][48][49][50][51] and the Schwarzian theory [52][53][54]. 6 As we will revi...…”
Section: Introductionmentioning
confidence: 99%
“…Both transform in the adjoint of U (N 3 ). Following [23] we can construct an exact collective description for T φ (2). We will extend the discussion of [23] by considering a model with a quartic potential.…”
Section: A "Planar Limit" For the Tensor Modelmentioning
confidence: 99%
“…The advantage of the restricted Schur polynomial basis follows because we are able, in the free theory, to compute correlators exactly. The results we will use are [23] O γ 1 γ 2…”
Section: Finite N Contributionsmentioning
confidence: 99%
“…The recent discovery of the relation between some sectors of Kronecker coefficients and Littlewood-Richardson numbers in the field of combinatorics and group theory. This is relevant for us since Kronecker coefficients organize the spectrum of eigenstates of free tensor models [29,30,31,32], whereas Littlewood-Richardson numbers have long been known to organize the spectrum of matrix models [34,35,36,37,38,39,40,41].…”
Section: Introductionmentioning
confidence: 99%